DEVELOPMENT OF MACARON CAKE WITH BLACK RICE FLOUR - Andian Ari Anggraeni, Intan Nurul Fiqri (Prosiding Pendidikan Teknik Boga Busana, 2020)
This study aims to develop cake products with the substitution of black rice flour. The cake product developed is Macaron Cake. Products that have been developed have been tested for preferences to assess community acceptance. Then the product is analyzed for nutrition. This study uses the R & D (Research & Development) method with the 4D development procedure (Define, Design, Develop, Diseminate). The panelists used in this study were 2 trained panelists, 30 semi-trained panelists, and 60 untrained panelists. The results of this study indicate that the amount of black rice flour substitution received is 40%. In the semi-trained panelist test, Macaron Cake’s development products were not significantly different from the reference products. As well as the panelists who were not trained, Macaron Cake’s development products were included in the preferred category with a score of 3 and above on all characteristics. Nutritional analysis shows that Macaron Cake products are classified as high-fat products. Keywords: Cake, Macaron Cake, Black Rice Flour INTRODUCTION Wheat is one of the main staple foods in Indonesia. Wheat is not a plant that can grow in Indonesia, therefore to meet the needs of wheat, Indonesia must import wheat from abroad. Australia is Indonesia’s largest wheat import destination country. Based on data from the Indonesian Wheat Flour Association (APTINDO) the volume of Indonesian wheat imports in 2017 rose by around 9% to 11.48 million tons from the previous year. (Badan Pusat Statistika, 2017). This increase in imports indicates that Indonesia is still very dependent on the presence of wheat which has resulted in low Indonesian food security. To deal with this, the Indonesian government held a local food consumption movement. Local food in Indonesia is quite diverse, ranging from cereals to tubers. Some local foods that are quite common in Indonesia include taro tubers, brown rice, corn, cassava and black rice. Black rice (Oryza sativa L.) is one of the local food